Chapter La recezione nella Russia del XVI secolo dei testi antilatini di Gregorio Palamas e Nilo Cabasilas - SCARPA, Marco (Biblioteca di Studi Slavistici, 2018)
Manuscript Moskva GIM Sin 383 was brought to Moscow in 1559 and was store in the library of Ivan the Terrible. There two copies of the codex were made: one is the manuscript Sin 45, the other - between 1559 and 1573 - was donated by Metropolitan Macarij to Josifo-Volokolamskij monastery, where the monk Evtimij Turkov copied it before 1573. Both manuscripts kept at the Josifo-Volokolamskij monastery are now lost. We know that in 1582 Ivan the Terrible used the manuscript Sin 383 (or Sin 45) in the dispute against Antonio Possevino.